2021
DOI: 10.1038/s41467-021-26743-5
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic transformation of cubic copper catalysts during CO2 electroreduction and its impact on catalytic selectivity

Abstract: To rationally design effective and stable catalysts for energy conversion applications, we need to understand how they transform under reaction conditions and reveal their underlying structure-property relationships. This is especially important for catalysts used in the electroreduction of carbon dioxide where product selectivity is sensitive to catalyst structure. Here, we present real-time electrochemical liquid cell transmission electron microscopy studies showing the restructuring of copper(I) oxide cubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(167 citation statements)
references
References 46 publications
7
160
0
Order By: Relevance
“…The recently performed electrochemical TEM investigations track the morphology transformation of CuO nanosheet into branched copper dendrites by using an in situ TEM E‐chip cell. [ 110 ] Similar attempts by operando TEM are also made on Cu 2 O cube [ 111 ] and Ag‐core/porous Cu‐shell nanoparticles, [ 71 ] where fragmentation of cubes into nanoporous frames and small nanoparticles, as well as the degradation of Cu catalyst promoted by local CO intermediate, are observed respectively. However, in those works, the image resolution only reaches ≈100 nm, yet far away from atomic scale.…”
Section: State‐of‐the‐art Operando Techniques For Monitoring Dynamic ...mentioning
confidence: 69%
See 2 more Smart Citations
“…The recently performed electrochemical TEM investigations track the morphology transformation of CuO nanosheet into branched copper dendrites by using an in situ TEM E‐chip cell. [ 110 ] Similar attempts by operando TEM are also made on Cu 2 O cube [ 111 ] and Ag‐core/porous Cu‐shell nanoparticles, [ 71 ] where fragmentation of cubes into nanoporous frames and small nanoparticles, as well as the degradation of Cu catalyst promoted by local CO intermediate, are observed respectively. However, in those works, the image resolution only reaches ≈100 nm, yet far away from atomic scale.…”
Section: State‐of‐the‐art Operando Techniques For Monitoring Dynamic ...mentioning
confidence: 69%
“…It is deduced that the reconstruction process was driven by highly negative potential and assisted by the CO intermediates. The negative potential provided adequate repulsive electrostatic forces to induce the lattice shrinking of Pd (111) surface and drove the Pd atoms migration from defect sites to assemble into more open (100) regions, during which the adsorbed CO intermediates reduced energy barrier of atomic migration. Moreover, the fast operando XAS experiments conducted by Wu et al demonstrated the conversion of initial Ag 2 O driven by the electrochemical reaction, leading to the reduction of oxidation state and twinning defect formation.…”
Section: Dynamic Evolution Of Non-copper Metal-based Nanocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[105] Most recently, the Cuenya group further demonstrated a dynamic morphology transformation of Cu 2 O to nanoporous cubic frames intermixing with re-deposited nanoparticle aggregates, leading to an enhanced production of hydrocarbons. [106] Hwang and co-workers revealed the electrochemical transformation of Cu 2 O into small, fragmented nanoparticles by HRTEM. Operando XAS showed the smaller fragmented Cu 2 O nanoparticles were reduced to metallic Cu during CO 2 R, which is prone to be re-oxidized at open circuit potential inside the electrolyte.…”
Section: Structure Reconstructionmentioning
confidence: 99%
“…Extensive studies have shown that fragmentation is the major degradation mechanism for Cu‐based nanostructures in CO 2 R. For instance, Buonsanti and co‐workers employed ex‐situ TEM to image the detachment of small Cu clusters from the surface of monodispersed Cu nanocubes (Figure 11), and concluded that potential‐driven nanoclustering is the predominant cause for CO 2 R deactivation [105] . Most recently, the Cuenya group further demonstrated a dynamic morphology transformation of Cu 2 O to nanoporous cubic frames intermixing with re‐deposited nanoparticle aggregates, leading to an enhanced production of hydrocarbons [106] . Hwang and co‐workers revealed the electrochemical transformation of Cu 2 O into small, fragmented nanoparticles by HRTEM.…”
Section: Dynamic Restructuringmentioning
confidence: 99%